As intervenções do Banco do Central do Brasil no mercado de câmbio e seus efeitos no nível intradiário da taxa de câmbio - Nogueira, Leandro Ribeiro (2014)
This work aims to investigate the effect of foreign exchange interventions by the Central Bank of Brazil on the intraday level of the exchange rate in Brazil. An event study approach is applied, correlating the tick-by-tick quotations of traded dollar future contracts at BM&FBOVESPA with the moment the interventions occurred, from October 2011 to March 2014. The analysis considered not only the moment of the intervention but also the moment of the announcement. Results indicated that the market reacts differently to each type of intervention, and reactions are sharper when interventions are not previously announced to the market. Interventions via currency swap or dollar spot generated significant and relevant effects on the level of the exchange rate. On the other hand, interventions that had sale/purchase auction with repurchase/resale commitment did not affect significantly the exchange rate.